Stereotactic radiosurgery planning of vestibular schwannomas: Is MRI at 3 Tesla geometrically accurate?. Issue 2 (16th February 2017) - Schmidt, M. A.; Wells, E. J.; Davison, K.; Riddell, A. M.; Welsh, L.; Saran, F.
Abstract : Purpose: MRI is a mandatory requirement to accurately plan Stereotactic Radiosurgery (SRS) for Vestibular Schwannomas. However, MRI may be distorted due not only to inhomogeneity of the static magnetic field and gradients but also due to susceptibility‐induced effects, which are more prominent at higher magnetic fields. We assess geometrical distortions around air spaces and consider MRI protocol requirements for SRS planning at 3 T. Methods: Hardware‐related distortion and the effect of incorrect shimming were investigated with structured test objects. The magnetic field was mapped over the head on five volunteers to assess susceptibility‐related distortion in the naso‐oro‐pharyngeal cavities (NOPC) and around the internal ear canal (IAC). Results: Hardware‐related geometric displacements were found to be less than 0.45 mm within the head volume, after distortion correction. Shimming errors can lead to displacements of up to 4 mm, but errors of this magnitude are unlikely to arise in practice. Susceptibility‐related field inhomogeneity was under 3.4 ppm, 2.8 ppm, and 2.7 ppm for the head, NOPC region and IAC region, respectively. For the SRS planning protocol (890 Hz/pixel, approximately 1 mm 3 isotropic), susceptibility‐related displacements were less than 0.5 mm (head), and 0.4 mm (IAC and NOPC). Large displacements are possible in MRI examinations undertaken with lower receiver bandwidth values, commonly used in clinical MRI. Higher receiver bandwidth makes the protocol less vulnerable to sub‐optimal shimming. The shimming volume and the CT‐MR co‐registration must be considered jointly. Conclusion: Geometric displacements can be kept under 1 mm in the vicinity of air spaces within the head at 3 T with appropriate setting of the receiver bandwidth, correct shimming and employing distortion correction.